IMPLEMENTATION OF LEGAL AND POLITICAL REFORMS IN UZBEKISTAN AND REFORMS AIMED AT FORMING A DEMOCRATIC SOCIETY (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the legal and political reforms implemented in the Republic of Uzbekistan during the years of independence, their essence, and their role in the formation of a democratic society. Particular attention is paid to the establishment of the rule of law, strengthening constitutional governance, reforming the judicial system, and developing civil society institutions. The study analyzes the significance of ongoing reforms for social development and the protection of human rights. It is emphasized that the reforms are being implemented in a systematic and consistent manner, aimed at democratizing public administration and ensuring fundamental freedoms.
Keywords: Uzbekistan; rule of law; democratic society; legal and political reforms; Constitution; judicial system; civil society; human rights; political reforms